Assessment of health risk induced by heavy metal contents in drinking water. (11th November 2022) - Shehu, Alma; Vasjari, Majlinda; Duka, Sonila; Vallja, Loreta; Broli, Nevila; Cenolli, Sadik
Abstract: Investigation of the quality of drinking water was carried out aiming to evaluate health risks and toxicity arising from the content of heavy metals. Samples were analysed for the content of Pb, Cd, Cr, Ni, Cu, Fe, Zn, Al, and Mn. Water quality and health risk assessment were evaluated by comparing the obtained data with current National, EU, and WHO regulations as well as by using the hazard quotient and cancer risk ( HQ and CR ). Results showed that Al (in one sample) and Ni (in five samples) exceeded the maximum allowed limits. Based on the metal pollution index, MPI, it was concluded that none of the samples exhibited 'very good quality' ( MPI > 0.3), whereas the overall quality of Glina bottled water was classified as toxic to humans and Trebeshina as moderately toxic. Selected samples exhibited no evident health risk to humans (HQ < 1). Among the toxic metals analysed, Ni, Cd, and Cr exhibited higher values of cancer risk index ( CR > 10 −4 ), whereas Pb exhibited the lowest value. Bottled water such as Qafeshtama, Lajthiza, Tepelena, Dukat, Spring, Living, and Aqua Pana as well as tap water collected in the area of Student's City in Tirana can be considered safe for human consumption. HIGHLIGHTS: Heavy metals can cause toxicity. Severe health effects are closely related to long term use. Toxicity and Cancer Risk indexes were used to evaluate water safety.